Kebersyukuran (Gratitude) Pada Remaja Dengan Orang Tua Pekerja Rantau - Da Silva, Satria; P. Panis, Marleny; Ratu, Feronika; Anakaka , Dian L. (Al Makki Publisher, 2025)
Adolescence is a critical phase characterized by the transition from childhood to adulthood, and is characterized by physical, mental, and psychological development. The role of parents in parenting is an important key in supporting adolescent growth. However, not all adolescents can live with their parents, as experienced by some adolescents in Besikama Village whose parents migrate due to economic demands. This condition has the potential to affect adolescents' emotional development, behavior, and gratitude. This study aims to find out how the description of gratitude of adolescents in Besikama Village who have parents as overseas workers in depth. This research uses descriptive qualitative methods with a total of 5 adolescents aged 15-18 years as participants. The data collection process used in-depth interviews. The validity of the data in this study uses Member Chek and Audit Trial techniques by interviewing adolescent children who are in Besikama Village and who have parents as overseas workers. The results showed that participants experienced emotional changes from sadness to acceptance, and were able to interpret the departure of parents positively. Their gratitude appears in the form of taking care of themselves, praying for their parents, following advice, actively worshiping, and maintaining good relationships with people around them. Gratitude is also expressed through self-reflection, changes in thinking, and willingness to accept life as it is. These findings suggest that gratitude is an adaptive strength for adolescents in dealing with separation from parents.